Analisis Pencegahan Demam Berdarah Dengue (DBD): Analysis of Dengue Hemorrhagic Fever (DHF) Prevention - Herawati, Asri; Febrianti, Dinda; Santoso, Doni; Brahmastha Arya Putra, Fathir; Gabe Sitorus, Giovaldo; Azmi Tasya, Rosifatul (Journal of Public Health Education, 2022)
Introduction: Dengue Hemorrhagic Fever (DHF) is one of the endemic diseases in Indonesia and several countries. Dengue Hemorrhagic Fever (DHF) is transmitted through mosquito bites from the Aedes genus, especially Aedes Aegypti. Objectives: DHF prevention efforts must be carried out now. What is held by the government is PSN (mosquito nest eradication) which is carried out by 3M plus (draining, closing, and utilizing and recycling used goods). Method: This study uses a descriptive research method that aims to analyze the prevention of Dengue Hemorrhagic Fever (DHF) in the working area of UPTD Puskesmas Sukmajaya District. Result: The results of the problem identification obtained are the lack of 3M behavior, the habit of hanging clothes in the house, and the lack of behavior in cleaning puddles, such as in dispensers, and water reservoirs behind the refrigerator, bird drinking places, and others. Conclusion: The priority of problem-solving is to provide an active method of activity by conducting public health facilitation activities as an effort to increase public awareness of the prevention behavior of Dengue Hemorrhagic Fever (DHF) through 3M.